Pengaruh Ukuran Ovarium dan Folikel terhadap Penampilan Reproduksi Pada Sapi PO dan SimPO di Kecamatan Jatinom, Kabupaten Klaten - Priyo Jr, Topas Wicaksono; Budiyanto, Agung; Kusumawati, Asmarani (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2020)
The increasing beef cattle population in Indonesia is not significantly with high demand of meat every year. The insignificant increasing in population is caused by fertility decreasing, infectious disease and the reduction amount of forage land. The factor which causes cattle fertility decreasing canâ€™t be separated from the ovarian and follicular diameter which have an effect on high various reproductive appearance. Parameters that used for knowing reproductive appearance of cattle are Service per Conception (S/C) and Calving Interval (CI). The aims of this study was to describe ovary sizes and follicular diameter in cattle, to describe ovary and follicular diameter toward S/C and CI variation. This research uses female cattle, 8 Simmental-PO (SimPO) and 9 Peranakan Ongole breeds (PO), multiparous, are not pregnant, 4-8 years old, Body Condition Score (BCS) 2.5-3.5, peak phase estrus, has no reproductive problems, clear recordings and live in the area of farmer in Jatinom District, Klaten Regency, Central Java Province. Cattle are examined for ovarian size and follicle size using ultrasonography. S/C and CI data were obtained from records of artificial insemination cards (AI). The data obtained were analyzed by t test. The results of this study showed there were no differences in the diameter of ovaries in the size of SimPO and PO cattle (P> 0.05), there were no differences in the diameter of SimPO and PO cattle follicles (> 0.05), there were differences in ovarian and follicular diameter sizes with respect to S/C and CI in cattle with good and bad reproductive performance (P <0.05). The conclusion of the study showed that there was no difference in ovarian and follicular diameter size in SimPO and PO cattle (P> 0.05) but there was an influence on S/C and CI (P <0.05).Â